а) 3x×(3x+7)-(3x+1)²=9x²+21x-(9x²+6x+1)=9x²-9x²+21x-6x-1=15x-1
б) (y-2)×(y+3)-(y-1)²=y²-y²+y+2y-6-1=3y-7
в) 4×(a+5)²-(3b-5)×(3b+5)= 4×(a²+10a+25)-(9b²-25)=4a²+40a+100-9b²+25=4a²-9b²+40a+125
г) 4b×(3b+6)-(3b-5)×(3b+5)=12b²+24b-(9b²-25)=3b²+24b+25
д) (p-2a)×(p+2a)-(p-a)×(p²+pa+a²)=p²-4a²-(p³-a³)=p²-4a²-p³+a³
Автор:
eleanor42Д)=p2+p2a−2ap−4a2+(−p+a)(p2+pa+a2)=p2+p2a−2ap−4a2+(−p+a)(p2+pa+a2)=p2−4a2+(−p+a)(p2+pa+a2)=p2−4a2−p3−p2a−pa2+ap2+a2p+a3=p2−4a2−p3−p2a−pa2+ap2+a2p+a3=p2−4a2−p3−pa2+a2p+a3=p2−4a2−p3+a3=p2−4a2−p3+a3=−p3+a3−4a2+p2
А) =3x(3x+7)−(9x2+6x+1)= 9x2+21x−9x2−6x−1=9x2+21x−9x2−6x−1=
21x−6x−1=15x−1
В) =4(a2+10a+25)−(3b−5)(3b+5)= 4a2+40a+100+(−3b+5)(3b+5)= 4a2+40a+100−9b2−15b+15b+25=4a2+40a+100−9b2−15b+15b+25=
4a2+40a+125−9b2=4a2+40a+125−9b2=4a2−9b2+40a+125
Г)=12b2+24b+(−3b+5)(3b+5)=12b2+24b−9b2−15b+15b+25=12b2+24b−9b2−15b+15b+25=
3b2+24b+25
в задании Б непонятное что то со скобками.
Если уравнение выглядит так y−2(y+3)−(y−1)2=, то…y−2(y+3)−(y2−2y+1)= y−2y−6−y2+2y−1=y−2y−6−y2+2y−1=
y−7−y2=y−7−y2=−y2+y−7
Автор:
donnabraunДобавить свой ответ
Предмет:
ИнформатикаАвтор:
cowboyОтветов:
Смотреть
Предмет:
ЛитератураАвтор:
magnoliaОтветов:
Смотреть
Предмет:
БиологияАвтор:
friskyt5nnОтветов:
Смотреть
Предмет:
ИнформатикаАвтор:
anteroОтветов:
Смотреть